Wykorzystanie spredu doskonale prognozowanego do weryfikacji hipotezy oczekiwań struktury czasowej stóp procentowych na rynku depozytów międzybankowych w Polsce - Blangiewicz, Maria; Miłobędzki, Paweł (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper is devoted to testing the expectations hypothesis of the term structure of interest rates in the Polish interbank market. When using weekly data over the period January 1999-April 2006, the null stating the slope equals unity in the regression of the perfect foresight spread on the actual spread is accepted for the shorter end of the term structure, and it is rejected for the longer end. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 46-55